A Study of Organizational Cynicism Among Employee Groups in a Multi-Campus Public University in Ghana: Does the Level of Education Matter? - Alhassan, Ibrahim (Advances in Social Sciences Research Journal, 2020)
This paper, which was part of a larger study, investigates the relationship between Organizational Cynicism (OC) and the level of education of three employee groups – Teaching Staff (TS), Non-Teaching Staff (NTS), and Senior Staff (SS) – of a multi-campus public University in Northern Ghana. Valid data were collected from 192 employees of the University for Development Studies (UDS) and analysed. A one-way ANOVA and Correlation Analyses were used to respectively determine the cynicism level of the three employee groups; and the relationship between the employees’ level of education and their cynical tendencies in the University. The study found a significant relationship between employees’ cynicism and their level of education; and that the two variables are inversely related. The findings also indicate that the SS group has the highest prevalence of cynicism in the University, followed by the TS, and then the NTS. Some theoretical and managerial implications are discussed.